Predictive Factors for Hearing Loss in Congenital Cytomegalovirus Infection - Virginia Corazzi; Lucia Belen Musumano; Andrea Migliorelli; Laura Negossi; Chiara Bianchini; Francesco Stomeo; Stefano Pelucchi; Andrea Ciorba (Audiology Research)
Objectives: The present study aims to identify potential predictive factors for developing sensorineural hearing loss (SNHL) in individuals with congenital Cytomegalovirus (cCMV) infection. Methods: A retrospective study was performed on 50 subjects with cCMV infection (symptomatic and asymptomatic), followed at the Audiology Service of Sant’Anna Hospital (University Hospital of Ferrara). The following data were analyzed: the type of maternal Cytomegalovirus (CMV) infection (primary versus non-primary), time of in utero infection, systemic signs and symptoms or laboratory test anomalies due to cCMV infection, and signs and symptoms of central nervous system (CNS) involvement at birth. In particular, brain ultrasonography and encephalic magnetic resonance imaging (MRI) were evaluated, searching for possible links between imaging findings and SNHL. Results: The statistical analysis showed a significantly higher risk of developing SNHL in subjects with signs and symptoms of CNS involvement at birth (p = 0.009 *). The presence of brain MRI abnormalities significantly influenced the onset of SNHL in patients with symptomatic cCMV infection (p = 0.012 *). Brain ultrasonography, the type of maternal CMV infection, systemic signs/symptoms and laboratory test anomalies at birth, and sex resulted in nonsignificant correlations in the analysis. Conclusions: The presence of neurological symptoms at birth and of detectable abnormalities in brain MRI are predictors of SNHL developing in symptomatic cCMV infection. Further investigation on this topic is necessary.